2015
DOI: 10.1002/ajh.24024
|View full text |Cite
|
Sign up to set email alerts
|

Deferiprone versus deferoxamine in thalassemia intermedia: Results from a 5‐year long‐term Italian multicenter randomized clinical trial

Abstract: In patients with thalassemia intermedia (TI), such as beta-TI, alpha-thalassemia (mainly HbH disease and mild/moderate forms of HbE/beta-thalassemia), iron overload is an important challenge in terms of diagnosis, monitoring, and treatment. Moreover, to date, the only possible chelators available are deferoxamine, deferasirox, and deferiprone. Here, we report the first 5-year long-term randomized clinical trial comparing the effectiveness of deferiprone versus deferoxamine in patients with TI. Body iron burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
1
36
2
1
Order By: Relevance
“…Heart damage was the leading cause of death in TM while cancer tops the list in TI and is potentially attributed to hepatocellular carcinoma. These differences may be attributed to varying iron chelation and HCV management practices spanning the cohort, which have considerably advanced since 1990 (Borgna-Pignatti et al, 2004a;Maggio et al, 2009a;Brittenham et al, 1994;Calleja et al, 1998;Cunningham et al, 2004;Ladis et al, 2011;Kwiatkowski et al, 2012;Zamani et al, 2015;Kutlar, 2007;Maggio et al, 2002Maggio et al, , 2009bCalvaruso et al, 2015;Wonke et al, 1998;Ambati et al, 2013;Modell et al, 2008;Cappellini et al, 2006;Aydinok et al, 2015;Cassinerio et al, 2015;Collett, 2014); Di Marco et al, 2010). Moreover, the mechanism of iron loading in TI and TM remain different with cardiac damage mostly apparent in TM patients while the liver is more affected in TI, with subsequent clinical consequences (Mariani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart damage was the leading cause of death in TM while cancer tops the list in TI and is potentially attributed to hepatocellular carcinoma. These differences may be attributed to varying iron chelation and HCV management practices spanning the cohort, which have considerably advanced since 1990 (Borgna-Pignatti et al, 2004a;Maggio et al, 2009a;Brittenham et al, 1994;Calleja et al, 1998;Cunningham et al, 2004;Ladis et al, 2011;Kwiatkowski et al, 2012;Zamani et al, 2015;Kutlar, 2007;Maggio et al, 2002Maggio et al, , 2009bCalvaruso et al, 2015;Wonke et al, 1998;Ambati et al, 2013;Modell et al, 2008;Cappellini et al, 2006;Aydinok et al, 2015;Cassinerio et al, 2015;Collett, 2014); Di Marco et al, 2010). Moreover, the mechanism of iron loading in TI and TM remain different with cardiac damage mostly apparent in TM patients while the liver is more affected in TI, with subsequent clinical consequences (Mariani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Standard iron chelation therapy in TM and TI patients (as indicated) was deferoxamine (DFO) as a subcutaneous infusion at a dose of 40-50 mg/kg/day from when it became available in 1965 until 1994. One hundred and fortyfour patients with TM (from September 1994) and 48 patients with TI (from January 2001) started/switched to deferiprone (DFP) treatment (Maggio et al, 2002) in the context of randomized multicentre clinical trials (Maggio et al, 2002(Maggio et al, , 2009bCalvaruso et al, 2015). Combination treatment with DFO and DFP was used from 1998 in TM patients with severe iron overload (Wonke et al, 1998), especially after reports of its effectiveness in controlling cardiac iron overload (Modell et al, 2008;Ambati et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The use of combined Fe chelators to prevent Fe-overload cardiomyopathy in thalassemia has been reported [34, 35]. Moreover, deferiprone is considered similar to deferoxamine in the treatment of thalassemia intermedia [36]. In addition, it has been shown that the oral Fe chelator deferasirox is able to inhibit NF- (nuclear factor-) kB dependent transcription without affecting its proximal activation, resulting in reduced TNF production from T cells stimulated in vitro.…”
Section: Chelating Agentsmentioning
confidence: 99%
“…21 Elalfy and et al in a study entitled "Efficacy and safety of a novel combination of two oral chelators Deferasirox/ Deferiprone over Deferoxamine/ Deferiprone in severely iron overloaded young beta thalassemia major patients" showed that both iron chelation combination regimens were equally effective in reducing iron overload and improving Quality Of Life. Deferoxamine/ Deferiprone combination proved superior in improving cardiac T2, treatment compliance, and patient's satisfaction with no greater adverse events.…”
Section: -11mentioning
confidence: 99%